FAKTOR FAKTOR YANG MEMPENGARUHI KEBERHASILAN PETANI PENANGKAR BAWANG MERAH DI KABUPATEN DELI SERDANG DAN KOTA MEDAN PROVINSI SUMATERA UTARA - Ameilia Zuliyanti Siregar; Nurliana Harahap; Yusra Muharami Lestari; Hamdan (Agrica Ekstensia, 2020)
One way to reduce onion imports due to high demand is by increasing the production of shallots in the lowlands. The research on onion breeder farmers conducted from April to July 2019 in Deli Serdang Regency and Medan City, North Sumatera Province aims to find out the success rate of onion breeder farmers and to determine factors of their ability, level of education, experience, income, technology, marketing, the role of government, the role of instructors and facilities and infrastructure that affect the success of onion grower farmers in North Sumatera. The research method used is descriptive quantitative, by gathering information observations, questionnaires, and interviews. The results showed the success rate of onion breeder farmers in both locations was very high, amounting to 83,7%. Based on tests conducted simultaneously showed an effect of 70% and partial testing showed three factors, such as: self of ability, the role of government and the role of the instructor did not significantly influence, when the level of education, experience, income, marketing, and technology showed a significant at p<0,05 on the success of onion grower farmers in Deli Serdang Regency and Medan City. Onion is a potential commodity that has prospects for development in North Sumatera.